Engineered wood products for circular construction: a multi-factor evaluation of lamination methods - Dan Bergsagel; Felix Heisel; Jasper Owen; Maxwell Rodencal (npj Materials Sustainability)
Abstract Engineered wood products (EWP) constitute a diverse range of structural element types attractive for the current construction industry. However, the use of permanent adhesive resins limits their ability to perform within a circular economy, and the glue-laminating process requires fossil-fuel-based adhesives that release potentially harmful gases. This paper presents a multi-factor evaluation of alternative lamination methods featuring an enhanced longitudinal shear transfer mechanism to produce beam elements with comparable structural performance while improving circular and environmental performance. The research focuses on EWP beam elements following three sequential studies: (1) an evaluation of interlocking surface patterns to improve non-adhesive lamination in two stages, interlocking pattern shapes (17 samples) and interlocking depths (24 samples); (2) an evaluation of structural performance of different lamination methods in bending (glue (GL), metal nails (MN), wood nails (WN), plastic straps (PS)) for a 4.5 ft two-layer beam formed of 2 × 4 lumber feedstock (using a 1/16in deep square grooved pattern and flat interface for reference (five samples each)), whereby the grooved interlocking samples with mechanical fasteners performed considerably well in both modulus of rupture (MOR) and modulus of elasticity (MOE) compared to the reference flat adhesive lamination method, 31% and 19% lower, respectively; and (3) a comparison of qualitative and quantitative parameters on structure, economy, environment and circularity. Together, the study identified a grooved shear interface with wood nail fasteners as a preferred lamination method for EWPs in circular construction (GrooveLam). These results are considered appropriate for the future development of larger dimension and longer length multi-lamination structural bending elements.